The Influence of Digital Marketing and Product Quality on the Development of MSMEs in Moderating Entrepreneurial Characteristics - Diansyah Diansyah; Ricky Hermawan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this research is to place entrepreneurial characteristics as a moderating variable on the influence of digital marketing and product quality on the development of SMEs. The research population is to improve the economy in Indonesia. Data collection techniques by distributing questionnaires through google form. The results of the study show that digital marketing, product quality and entrepreneurial characteristics have a positive and significant effect on the development of MSMEs, the method of entrepreneurial characteristics on the influence of digital marketing has no effect on the development of MSMEs. Moderation of entrepreneurial characteristics on the effect of product quality has no effect on the development of SMEs which are moderated by entrepreneurial characteristics.